2022
DOI: 10.3390/su14159772
|View full text |Cite
|
Sign up to set email alerts
|

Inclined Layer Method-Based Theoretical Calculation of Active Earth Pressure of a Finite-Width Soil for a Rotating-Base Retaining Wall

Abstract: In this study, we evaluated the active earth pressure on a retaining wall with a narrow cohesive fill under the rotation about the base mode. Under these conditions, Rankine’s and Coulomb’s earth pressure theories are not strictly effective. To improve the traditional earth pressure calculation methods (Rankine and Coulomb methods) and deduce the active earth pressure under the rotation about the base mode, here, we propose a new calculation method that incorporates the effects of wall displacement, soil archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…The figure shows that there are many cross distribution phenomena of sliding surfaces in the damaged wedge. Some scholars (Que et al [23] and Zhang et al [22]) refer to these sliding surfaces as sub-sliding surfaces.…”
Section: Relief Shelf Lengthmentioning
confidence: 99%
“…The figure shows that there are many cross distribution phenomena of sliding surfaces in the damaged wedge. Some scholars (Que et al [23] and Zhang et al [22]) refer to these sliding surfaces as sub-sliding surfaces.…”
Section: Relief Shelf Lengthmentioning
confidence: 99%
“…The adjacent underground structures prevent the sliding surface in the backfill from fully developing to the backfill surface, resulting in a Sustainability 2022, 14, 12699 2 of 18 large difference between the earth pressure behind the wall and that in the semi-infinite soil case. Several studies have demonstrated that the active earth pressure acting on the retaining wall decreases with the narrowing of the backfill behind the wall [3,[5][6][7][8][9][10][11][12]. In addition, some scholars have discussed the shape of the slip surface in the soil under the condition of narrow backfill.…”
Section: Introductionmentioning
confidence: 99%